Effectiveness and safety of pelareorep plus chemotherapy versus chemotherapy alone for advanced solid tumors: a meta-analysis - Xie, Renxian; Huang, Hongxin; Chen, Tong; Huang, Xuehan; Chen, Chuangzhen (Frontiers in Pharmacology, 2023)
Pelareorep is an oncolytic virus that causes oncolytic effects in many solid tumors, and it has shown therapeutic benefits. However, few studies have compared pelareorep combined with chemotherapy to traditional chemotherapy alone in advanced solid tumors. Consequently, we intended to evaluate the effectiveness and safety of pelareorep plus chemotherapy in this paper. Methods: We searched four databases including PubMed, Embase, Cochrane Library and Web of Science comprehensively for studies comparing pelareorep combined with chemotherapy to chemotherapy alone in the treatment of advanced solid tumors. The outcomes measures were 1-year overall survival (OS), 2-year OS, 4-month progression-free survival (PFS), 1-year PFS, objective response rate (ORR), any-grade adverse events (any-grade AEs), and severe AEs (grade ≥ 3). Results: There were five studies involving 492 patients included in the study. Combination therapy did not significantly improve clinical outcomes in terms of 1-year OS (RR = 1.02, 95%CI = [0.82-1.25]), 2-year OS (RR = 1.00, 95%CI = [0.67-1.49]), 4-month PFS (RR = 1.00, 95%CI = [0.67-1.49]), 1-year PFS (RR = 0.79, 95%CI = [0.44-1.42]), and ORR (OR = 0.79, 95%CI = [0.49-1.27]) compared to chemotherapy alone, and the subgroup analysis of 2-year OS, 1-year PFS, and ORR based on countries and tumor sites showed similar results. In all grades, the incidence of AEs was greater with combination therapy, including fever (RR = 3.10, 95%CI = [1.48-6.52]), nausea (RR = 1.19, 95%CI = [1.02-1.38]), diarrhea (RR = 1.87, 95%CI = [1.39-2.52]), chills (RR = 4.14, 95%CI = [2.30-7.43]), headache (RR = 1.46, 95%CI = [1.02-2.09]), vomiting (RR = 1.38, 95%CI = [1.06-1.80]) and flu-like symptoms (RR = 4.18,). However, severe adverse events did not differ significantly between the two arms. Conclusion: Peleareorep addition to traditional chemotherapy did not lead to significant improvements in OS, PFS, or ORR in advanced solid tumor patients, but it did partially increase AEs in all grades, with no discernible differences in serious AEs. Therefore, the combination treatment is not recommended in patients with advanced solid tumors. Systematic Review Registration: This meta-analysis was already registered in PROSPERO, identifier [CRD42023400841].